(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article explores the transformation of human education within the context of Western society. It delves into the historical development of education, the changing curriculum and pedagogical approaches, the impact of technology, and the pursuit of accessibility, diversity, and inclusivity. The article also highlights the importance of lifelong learning and innovation in shaping the future of education.